A THEORETICAL AND COMPARATIVE ANALYSIS OF VERB VALENCY IN ENGLISH AND RUSSIAN (Journal of Universal Science Research, 2025)
This article explores the concept of verb valency, which refers to the number of arguments a verb can take. It outlines the history of valency theory presented by Lucien Tesnière in 1959. The article also contrasts the valency systems of English and Russian, highlighting the structural and typological distinctions between the two languages.